Antimicrobial stewardship: Strategies for a global response - Jenny Grunwald; John Zervos; Marcus Zervos; Indira Brar (Wolters Kluwer Medknow Publications, 2014)
The increasing antimicrobial resistance worldwide, combined with dwindling antimicrobial armamentarium, has resulted in a critical threat to the public health and safety of patients. To combat this hazard, antimicrobial stewardship programs (ASPs) have emerged. Antimicrobial stewardship programs prevent or slow the emergence of antimicrobial resistance by coordinated interventions designed to optimize antimicrobial use to achieve the best clinical outcomes and limiting selective pressures that drive the emergence of resistance. This also reduces excessive costs attributable to suboptimal antimicrobial use. Even though an ideal effective ASP should incorporate more than one element simultaneously, it also requires a multidisciplinary team, which should include an infectious diseases physician, a clinical pharmacist with infectious diseases training, infection control professionals, hospital epidemiologist, a clinical microbiologist and an information specialist. However, for antimicrobial stewardship (AMS) programs to be successful, they must address the specific needs of individual institutions, must be built on available resources, the limitations and advantages of each institution, and the available staffing and technological infrastructure.